Drivers of diurnal rest site selection by spotted hyaenas. (11th September 2017) - Kushata, J. N. T.; Périquet, S.; Tarakini, T.; Muzamba, M.; Mafuwa, B.; Loveridge, A. J.; Macdonald, D. W.; Fritz, H.; Valeix, M.
Abstract: Rest sites are key locations to many animals but their selection has been poorly studied in large carnivores. We investigated seasonal diurnal rest site selection by spotted hyaenas ( Crocuta crocuta ) in Hwange National Park, Zimbabwe. We assessed the effects on hyaena diurnal rest site selection of (1) distance to the nearest waterhole, as waterholes can be considered prey hotspots in the study ecosystem, (2) habitat type and vegetation characteristics, in particular visibility as it influences detection risk and shade for thermoregulation, (3) location within the core territory of their main competitor/predator, the African lion ( Panthera leo ), where encounter risk would be higher, (4) distance to the closest lion and (5) distance to the nearest road as they can facilitate travelling by carnivores. We defined rest sites as midday locations of hyaenas equipped with GPS collars. Hyaenas preferred to rest in woodland areas with low visibility, close to roads and far from a lion. Distance to the nearest waterhole and location within lion core territory did not affect hyaena rest site selection. Overall, our study points to the combined importance of the structure of the vegetation (providing safety and shade), the availability of roads (to move through and exploit this bushed environment) and the avoidance of proximity to lions. Abstract : Numerous nocturnal species need to find locations to rest during the day that provide both shelter from the weather (e.g. thermoregulation) and safety from potential predators. The characteristics and factors influencing the selection of such diurnal rest site are poorly understood, especially in large carnivores. Using GPS collars deployed on spotted hyaenas ( Crocuta crocuta ), we provide a description of their diurnal rest sites and identify factors influencing their selection. We found that diurnal rest site selection was mainly influenced by the vegetation density, most probably related to thermoregulation. While hyaenas equally used locations within and outside lion ( Panthera leo, hyaenas' competitor and predator) home range core areas, they tend to avoid resting in locations where lions had been close to within the last 24 hours. Our results suggest that hyaena diurnal rest site selection is mainly driven by habitat characteristics and the short‐term risk of encountering lions rather than the long‐term predation risk by lions.